Optimization of dye extraction from purple cabbage and cordyline fruticosa in dye-sensitized solar cell - Ainfatin K.R.; Syahida S.; Mohd Azman H.; Nadhrah M.Y.; Najiha H. (Trans Tech Publications Ltd, 2024)
Indexed by SCOPUS/ERA